TESL pre-service teachers’ motivation to integrate critical thinking in their teaching - Mansor, Majdina; Khalid, Madihah (2017)
This study examined TESL pre-service teachers’ motivation level to integrate critical thinking in their teaching and the influence of ‘year of study’ towards their motivation. A total of 106 TESL students from a Malaysian public university participated in a questionnaire survey that measures motivation on a 5-point Likert scale. The data were analysed quantitatively using descriptive statistics and One-Way ANOVA. The results indicated that TESL pre-service teacher motivation to integrate critical thinking in their instruction is high.